Rheumatic Heart Disease Management: Patients’ Experiences, Health Practices, and Role Performance - Tolentino, Regina; Margallo, Virginia (JPAIR Multidisciplinary Research, 2019)
Rheumatic Heart Disease (RHD) continues to be a major health hazard in most developing countries as well as sporadically in developed economies. This study aimed to determine the drug regimen therapy of rheumatic heart disease patients and the effects of the illness physically, emotionally, and socially. This qualitative and quantitative study documented the drug regimen therapy management of twenty-seven (27) patients among the eighty-two (82) patients currently receiving the drug regimen for Rheumatic Heart Disease at the Out-Patient Department (OPD) of Cotabato Regional and Medical Center (CRMC) through the interview, observation, self-made questionnaire and focus group discussion. The study found out that RHD patients, who were mostly housewives, feel strong and healthy when complying with the date of Benzathine penicillin and experienced heart palpitation if unable to come on their visit on the 21st or 28th of the month. The effect of RHD physically is feeling of fatigue on the emotional aspect, anxiety in the social aspect, and avoid activities. The current role performance mostly is housewives. On health services received at OPD CRMC mostly, they received an injection of Benzathine Penicillin.  The majority have a monthly check-up as their priority in their health practice.
Keywords: Health Science; Rheumatic Heart Disease; Quantitative-qualitative design; Cotabato Regional; Medical Center; Cotabato City; Philippines